Study on the Implementation of the Dengue Hemorrhagic Fever Vector Control Program in the Working Area of the Pare Health Center Kediri Regency - Itsna Nurul Auliya; Narwati; Irwan Sulistio; Windri Khusuma Pratiwi (Public Health Research Development, 2024)
The main problem in controlling dengue in Pare District is the inconsistent and inconsistent implementation of the Mosquito Nest Eradication program and the lack of comprehensive counseling to the community. In addition, monitoring of larvae that do not meet standards also contributes to the increase in dengue cases. The purpose of the study is to examine the implementation of the dengue control program in the Working Area of the Pare Health Center, Kediri Regency. The type of research is qualitative descriptive. The location of the research was carried out in the Working Area of the Pare Health Center, Kediri Regency. The research informants were divided into two, namely key informants and supporting informants with a total of 22 informants. Sampling was carried out using purposive sampling. The data collection technique uses interviews and observations. The data obtained were analyzed descriptively. The results of the research are the Dengue Vector Control Program at the Pare Health Center including Standard Operational Prpcedure, counseling, control of physical, biological, chemical, and integrated methods in the good category. Meanwhile, efforts to report and evaluate dengue vector control are in the category of lacking. The conclusion of the study shows that efforts to control dengue vectors in the Working Area of the Pare Health Center are still not optimal and need to be improved, both in terms of the implementation of various control methods, compliance with SOPs, and a better evaluation system. Suggestions for the Pare Health Center to increase preparedness for epidemiological investigations, counseling, periodic Mosquito Nest Eradication, as well as the implementation and socialization of the household mosquito breeding ground eradication program. Periodic evaluations such as efficacy and resistance tests need to be carried out.